2021
DOI: 10.3389/fcell.2021.650004
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-coding RNA RUNDC3A-AS1 Promotes Lung Metastasis of Thyroid Cancer via Targeting the miR-182-5p/ADAM9

Abstract: Long non-coding RNAs (lncRNAs) have been identified as influential indicators in variety of malignancies. Among which, LncRNA RUNDC3A-AS1 is reported to upregulate in thyroid cancer. However, the expression pattern and the pathological function of lncRNA RUNDC3A-AS1 in thyroid cancer is unclear. In this study, we examined the expression levels of lncRNA RUNDC3A-AS1 in the thyroid cancer tissues and cell lines via RT-qPCR analysis. The effects of RUNDC3A-AS1 on thyroid cancer cell metastasis were detected by tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In many cancers, long non-coding RNAs (lncRNAs) of >200 nt are pivotal regulators [ 6 ]. This is supported by evidence that an increase in the expression levels of lncRNAs, including RUNDC3A-AS1 [ 7 ], CCDC26 [ 8 ], XIST [ 9 ], and TUG1 [ 10 ] leads to an unfavorable THCA prognosis. LINC00115 , an lncRNA, was originally identified as a possible biomarker for bladder [ 11 ] and lung cancers [ 12 ].…”
Section: Introductionmentioning
confidence: 88%
“…In many cancers, long non-coding RNAs (lncRNAs) of >200 nt are pivotal regulators [ 6 ]. This is supported by evidence that an increase in the expression levels of lncRNAs, including RUNDC3A-AS1 [ 7 ], CCDC26 [ 8 ], XIST [ 9 ], and TUG1 [ 10 ] leads to an unfavorable THCA prognosis. LINC00115 , an lncRNA, was originally identified as a possible biomarker for bladder [ 11 ] and lung cancers [ 12 ].…”
Section: Introductionmentioning
confidence: 88%
“…SBF2-AS1 can also affect the malignant phenotype of non-small cell lung cancer (NSCLC) by participating in miR-338-3p/ADAM17 axis (37). However, RUNDC3A-AS1 has not been extensively studied, and it was currently discovered that RUNDC3A-AS1 regulated the malignant progression of thyroid cancer and can promote lung metastasis by targeting miR-182-5p/ADAM9 (38,39). New research has shown that miR-338-3p suppresses the metastasis of lung cancer by influencing the MAPK signaling pathway or targeting KIF2A (40,41).…”
Section: B Amentioning
confidence: 99%